2016
DOI: 10.1002/1873-3468.12384
|View full text |Cite
|
Sign up to set email alerts
|

OPA1 functionally interacts with MIC60 but is dispensable for crista junction formation

Abstract: Edited by Miguel De la RosaRemodeling of crista junctions (CJs) is observed in numerous human disorders and during apoptosis. The functional interplay of OPA1 and MIC60, two key players in this context, is unclear. We show that OPA1 modulates cristae morphology but is dispensable for CJ formation. MIC60 is strongly enriched at CJs, whereas OPA1 is distributed evenly across the inner membrane. MIC60 levels are increased in OPA1À/À cells which show increased cellular resistance to apoptosis induction. Endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
70
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 60 publications
7
70
0
2
Order By: Relevance
“…This comprehensive morphometry analysis revealed that (1) OPA1 is the sole regulator of CLW and CJW, (2) OPA1 and MIC60 lie in the same pathway controlling CJ number and stability, and (2) surprisingly, OPA1 is epistatic to MIC60. While this work was under revision, Barrera et al., (2016) confirmed that OPA1 and MIC60 interact physically and that levels of the former affect CJ number. However, whether they lie in the same genetic pathway and how they are relatively positioned in the control of the multiple parameters of cristae shape was not addressed (Barrera et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This comprehensive morphometry analysis revealed that (1) OPA1 is the sole regulator of CLW and CJW, (2) OPA1 and MIC60 lie in the same pathway controlling CJ number and stability, and (2) surprisingly, OPA1 is epistatic to MIC60. While this work was under revision, Barrera et al., (2016) confirmed that OPA1 and MIC60 interact physically and that levels of the former affect CJ number. However, whether they lie in the same genetic pathway and how they are relatively positioned in the control of the multiple parameters of cristae shape was not addressed (Barrera et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While this work was under revision, Barrera et al., (2016) confirmed that OPA1 and MIC60 interact physically and that levels of the former affect CJ number. However, whether they lie in the same genetic pathway and how they are relatively positioned in the control of the multiple parameters of cristae shape was not addressed (Barrera et al., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Also the mitochondrial dynamin-like OPA1 GTPase has been shown to play a crucial role in cristae remodelling and mitochondrial fusion1718205152. Furthermore, a direct involvement of the MICOS component Mic10 in creating membrane curvature was recently demonstrated3338 indicating that Mic10 directly participates in mitochondrial membrane remodelling by oligomerization.…”
Section: Discussionmentioning
confidence: 99%
“…Cristae are linked to the IBM via tubular openings of defined diameter termed crista junctions (CJs)710. It has been proposed that cristae formation and dynamics may be connected to the mitochondrial fusion and fission machineries171819. Perturbations of these processes are observed in numerous pathologies including neurodegenerative diseases and cancer124.…”
mentioning
confidence: 99%
See 1 more Smart Citation